Interpretasi Kisah Luqman dalam Al-Qur’an pada Realitas Agama dan Sosial (Pendekatan Sastra Kebahasaan) - Sharikhul Hanif; Muhammad Irsyad (Hikmah, 2022)
This study aims to analyze the story of Luqman as contained in Surah Luqman verses 12-19 and interpret it with the moral formation of human life. Luqman's story will be studied through a literary-language approach to mimetic criticism to find the reality that exists in real life. This approach focuses on the study of the relationship of literary works with reality or reality outside of literary works. This approach has an influence on the reader in the application of life values ​​which is a form of implementation of the story contained in Surah Luqman verses 12-19. The implementation can be in the form of attitudes and actions that are adapted to the moral message contained in Surah Luqman verses 12-19. The results of the study indicate that the literary-linguistic approach can reveal the message contained in the surah as the purpose of its revelation to humans. The reality expressed in Luqman's story in Surah Luqman verses 12-19 is religious, social, and educational. The reality of religion is the relationship between humans and God, social reality is the relationship between humans and other humans. The reality of education about the role of fathers teaches the value of the noble character to children.